Enhancing process optimization through adaptive jig design in lean manufacturing: insights from Universitas Mercu Buana's laboratory - Qulub, Irkham Syifaul; Herlambang, Hendi; Amrina, Uly; Ikatrinasari, Zulfa Fitri (Operations Excellence: Journal of Applied Industrial Engineering, 2024)
This study aims to enhance efficiency in the Lean Manufacturing practicum at the Lean Manufacturing Laboratory of Universitas Mercu Buana by applying PDCA (Plan-Do-Check-Act) and TRIZ (Theory of Inventive Problem Solving) methods. The primary focus was the design and implementation of a flexible jig tool to reduce processing time and increase precision in the vacuum, trimming, and assembly stages designing and implementing. Results showed that the flexible jig reduced process time by 37.8%, from 1431 seconds to 890 seconds, and improved the level of automation from fully manual to the use of flexible tools. Further evaluation revealed significant gains in productivity. The study utilized tools such as Value Stream Mapping (VSM), Operation Process Chart (OPC), and the seven waste concepts within the PDCA framework to identify key issues in the manufacturing process. The application of TRIZ principles in tool design also significantly enhanced production efficiency. This research presents compelling evidence that systematic approach like PDCA and creative methodologies for instance TRIZ can substantially improve operational performance in light manufacturing practicums. Additionally, it highlights the important role of higher education in fostering technological innovation and industry collaboration to tackle evolving manufacturing challenges.